Shifts Between Sugar Kelp and Turf Algae in Norway: Regime Shifts or Fluctuations Between Different Opportunistic Seaweed Species? - Christie, Hartvig; Andersen, Guri S.; Bekkby, Trine; Fagerli, Camilla W.; Gitmark, Janne K.; Gundersen, Hege; Rinde, Eli (Frontiers in Marine Science, 2019)
Around year 2000, sugar kelp (Saccharina latissima) forests were observed to disappear in southern parts of Norway, being replaced by mats of turf algae (i.e., filamentous ephemeral algae) loaded with sediments. Among more than 600 stations covering 35 000 km of coastline, about 80% on the Skagerrak coast and about 40% on the North Sea coast were dominated by turf. Various types of turf algae replaced S. latissima in a discontinuous pattern. This large spatial scale event was reported as a possible irrevocable regime shift, not caused by a single factor but related to multiple stressors, where eutrophication and ocean warming were proposed to be the most important. Recent observations have however, revealed that the seabed state has flipped back and forth between sugar kelp and turf algae in several areas and on temporal scales spanning from seasons to years. The relative abundance of S. latissima at monitoring sites at the Norwegian southern coast has fluctuated dramatically during the last 12 years, varying from sparse to common at several of these sites. In 2016, sugar kelp abundance had increased in more than half of the sites, compared to earlier years. Our monitoring data as well as other field observations and field experiments question the regime shift paradigm. Although traditionally considered as a perennial macrophyte, several of our studies indicate that sugar kelp possesses many of the characteristic traits of an opportunistic species, such as high dispersal potential and colonization rate, which enables the species to rapidly colonize available substrate. However, where turf algae persist, space for recolonization of sugar kelp will most likely be minor. In this paper we explore the spatial and temporal shift dynamic between sugar kelp and turf algae based on monitoring data and other studies. Based on a synthesis of mapped fluctuations between the two states, and studies on sugar kelps recolonization abilities, we discuss prerequisites and drivers for an irrevocable regime shift or a continuation of natural fluctuations, as well as possible mitigation actions.